Phaeochromocytoma and catecholamine induced cardiomyopathy presenting as heart failure. Issue 4 (April 1990) - Sardesai, S H; Mourant, A J; Sivathandon, Y; Farrow, R; Gibbons, D O
Abstract : Phaeochromocytoma is rare and usually presents as paroxysmal or sustained hypertension; none the less, it can also cause severe acute pulmonary oedema in normotensive individuals. Six patients with phaeochromocytoma presenting in Cornwall and West Devon between 1982 and 1986 are described. Five of them died of pulmonary oedema within 24 hours of the onset of symptoms. At necropsy all five had normal sized hearts and in the four hearts examined by histology there was evidence of catecholamine induced heart disease in the form of focal myocardial necrosis. The sixth patient presented with arterial spasms and pulmonary oedema. Surgical removal of the causative tumour was successful in this patient.